The Role of Jinhuang Powder to Prevent Adverse Effects of Subcutaneous Injection of Enoxaparin Sodium - Meng Zhang; Xiang Zhang; Chunlan Wang; Yangfang Shen; Jianan Fu (Emergency Medicine International)
Objective. To determine the role of Jinhuang Powder to prevent adverse effects of subcutaneous injection of enoxaparin sodium. Methods. The clinical data of 97 patients with cervical cancer who were treated with subcutaneous injection of enoxaparin through the lower margin of the deltoid muscle of the upper arm in Zhejiang Tumor Hospital from August 2020 to August 2021 were retrospectively analyzed. All patients were divided into the control group (n = 39) and the research group (n = 58) according to the different use time periods of Jinhuang Powder. The research group was treated with Jinhuang Powder and enoxaparin sodium at the same time. The control group started to use Jinhuang Powder after the adverse reactions occurred. The induration, subcutaneous bleeding events, and pain were statistically analyzed. Results. The incidence of induration (3.4% vs 15.4%, P=0.036) and subcutaneous hemorrhage (37.9% vs 76.9%, P=0.003) in the research group was significantly lower than that in the control group. The pain in the research group was lighter than that in the control group (grade 0–4 pain: 70% vs 28.2%, 19% vs 30.8%, 8.6% vs 23.1%, 1.7% vs 12.8%, 1.7% vs 5.1%, P=0.001). Conclusion. Preventive use of Jinhuang Powder can significantly reduce the incidence of subcutaneous induration and subcutaneous bleeding and can effectively alleviate the local pain of injection. It is worthy of further study to clarify its role and mechanism.